2016
DOI: 10.2196/resprot.4841
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gaming for Improving the Functioning of People With Traumatic Brain Injury: Protocol of a Feasibility Study

Abstract: BackgroundTraumatic brain injury (TBI) is a critical public health problem. The recovery process for people with TBI is typically slow and dependent on complex and intensive assisted rehabilitation programs.ObjectiveTo evaluate the effects and feasibility of digital games for cognitive functioning and general well-being among people with traumatic brain injury.MethodsThis is a single-site feasibility study conducted in Finland, which uses a pragmatic, randomized controlled trial with three arms, and will recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…The study includes a three-arm, parallel, and randomized clinical trial examining the effectiveness and feasibility of digital gaming for improving cognitive functioning and general well-being in people with TBI. The full study design and detailed description of the study methods can be found elsewhere [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study includes a three-arm, parallel, and randomized clinical trial examining the effectiveness and feasibility of digital gaming for improving cognitive functioning and general well-being in people with TBI. The full study design and detailed description of the study methods can be found elsewhere [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our preliminary power calculations (see [ 48 ]), the sample size was expected to be 30 in each group, which is not very strong but reasonable enough for a feasibility study aiming to detect changes within a group between baseline and follow-up outcome measurements with an expected attrition rate close to 0%. However, some patients changed their minds regarding their participation before signing a consent form and dropped out of the recruitment process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…El uso del juego está en la línea de propuestas de implementación de programas de realidad virtual que han evidenciado mejoras en la rehabilitación de DCA (Lloréns, Colomer-Font, Alcaniz, y Noé-Sebastián, 2013;Putnam, Cheng, y Seymour, 2014;Valimaki et al, 2016), y la utilización de juegos en la rehabilitación cognitiva (Christensen, 2000;Shapi'i, Mat Zin, y Elaklouk, 2015).…”
Section: Recursos Metodológicosunclassified